The Pursuit of Noninvasive Diagnosis of Lung Cancer - Atwater, Thomas; Cook, Christine M.; Massion, Pierre P. (Seminars in Respiratory and Critical Care Medicine, 2016)
The noninvasive diagnosis of lung cancer remains a formidable challenge. Although tissue diagnosis will remain the gold standard for the foreseeable future, questions pertaining to the risks and costs associated with invasive diagnostic procedures are of prime relevance. This review addresses new modalities for improving the noninvasive evaluation of suspicious lung nodules. Ultimately, the goal is to translate early diagnosis into early treatment. We discuss how biomarkers could assist in distinguishing benign from malignant nodules and aggressive from indolent tumors. The field of biomarkers is rapidly expanding and progressing, and efforts are well underway to apply molecular diagnostics to address the shortcomings of current lung cancer diagnostic tools.
Keywords: early detection; clinical utility; biomarkers; indeterminate pulmonary nodule